A loading-dependent model of critical resolved shear stress. (October 2018) - Cai, Y.; Wu, H.A.; Luo, S.N.
Abstract: A quantitative model is developed to describe the critical resolved shear stress (CRSS), which is required for homogeneous partial dislocation nucleation in Lennard − Jones single crystals under general loading conditions, and to predict the slip systems to be activated. In this model, CRSS depends on actual loading, i.e., hydrostatic and all deviatoric stress components, and has directionality. Systematic molecular dynamics simulations are conducted to validate the model under different loading conditions including pure shear, and uniaxial stress (compression and tension) without and with initial hydrostatic pressure applied, and demonstrate that this model predicts exact slip systems and CRSS accurately. The relative orientation between loading direction and slip direction plays an important role in the compression–tension asymmetry in yield strength. On the other hand, Schmid's law fails for some loading conditions, and a new definition of the Schmid factor is proposed. Highlights: Acritical resolved shear stressmodel for homogeneous partial dislocation nucleation. The model yields good accuracy, and predicts the exact activated slip systems. Compression–tension asymmetry is well correlated to the CRSS directionality. A new definition of Schmid factor to correlate orientation and yield strength.